Long-Term Recording of LTP in Cultured Hippocampal Slices. Issue 4 (2002) - Shimono, Ken; Baudry, Michel; Ho, Lam; Taketani, Makoto; Lynch, Gary
Abstract : Long-term potentiation (LTP) was elicited by high frequency stimulation in hippocampal slices cultured on multi-electrode arrays. LTP lasting more than 1 h was recorded in 75% of slices, and a significant number of slices exhibited a non-decaying LTP that lasted more than 48 h. LTP induction was completely and reversibly blocked by an antagonist of the NMDA receptor, APV. Our results suggest the possibility of using chronic recording in hippocampal slices cultured on multi-electrode arrays to study the mechanisms underlying LTP maintenance and stabilization.